Statutory Interpretation in a New Nutshell - Sullivan, Ruth (The Canadian Bar Review, 2003)
This article attempts to update a Canadian classic - the realist account of statutory interpretation published by John Willis in the Canadian Bar Review in 1938. Willis' insights are compelling and they remain relevant today. However, by focusing on the rhetoric of statutory interpretation, by far its weakest point, Willis disregards the considerable work that goes on when statutory interpretation is well done. This article draws attention to that work. Part 2 looks at the kinds of analyses relied on by good interpreters to establish that elusive goal, the intention of the legislature. These include textual, purposive, scheme, policy and consequential analysis. Part 2 examines the difference between easy and hard cases, then focuses on the techniques used by interpreters to carry out the different kinds of analyses and how these relate to the formal rules. Part 3 looks at the range of arguments interpreters may construct based on their preliminary analysis. Not every argument in statutory interpretation is about the meaning of words. Interpreters also confront drafter's mistakes, gaps in the legislative scheme, overlap and conflict, and language that is over- or under-inclusive. The structure of these different kinds of arguments is set out and illustrated in Part 3.